Denosumab Treatment Does Not Halt Progression of Bone Lesions in Multicentric Carpotarsal Osteolysis Syndrome - Melissa A. Lerman; Michael Francavilla; Lindsay Waqar‐Cowles; Michael A. Levine (JBMR Plus, 2023)
ABSTRACT Here we report the use of denosumab, a monoclonal antibody against receptor activator of nuclear factor κB ligand (RANKL), as monotherapy for multicentric carpotarsal osteolysis syndrome (MCTO) in an 11.5‐year‐old male with a heterozygous missense mutation in MAFB (c.206C>T; p.Ser69Leu). We treated the subject with 0.5 mg/kg denosumab every 60–90 days for 47 months and monitored bone and mineral metabolism, kidney function, joint range of motion (ROM), and bone and joint morphology. Serum markers of bone turnover reduced rapidly, bone density increased, and renal function remained normal. Nevertheless, MCTO‐related osteolysis and joint immobility progressed during denosumab treatment. Symptomatic hypercalcemia and protracted hypercalciuria occurred during weaning and after discontinuation of denosumab and required treatment with zoledronate. When expressed in vitro, the c.206C>T; p.Ser69Leu variant had increased protein stability and produced greater transactivation of a luciferase reporter under the control of the PTH gene promoter than did wild‐type MafB. Based on our experience and that of others, denosumab does not appear to be efficacious for MCTO and carries a high risk of rebound hypercalcemia and/or hypercalciuria after drug discontinuation. © 2023 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.